Eleventh Five Year Plan 2007-2012 and Annual Plan 2007-2008 (Draft) Volume- II (Annexures) - Planning Commission (Planning Commission, 2007)
Agriculture And Allied Activities Draft Eleventh Five Year Plan (2007- 12) And Annual Plan (2007-08) -Proposed Outlays (From State Budget) Draft Eleventh Five Year Plan (2007-12) And Annual Plan - 2007- 08 - Proposed Outlays (From Public Sector Enterprises) Draft Eleventh Five Year Plan (2007-12) And Annual Plan - 2007- 08 - Proposed Outlays (Rural Local Bodies)
Government of Kerala